Stability study of slopes parallel to the Al-Meshar Road at Bir Al-Ghanam Area (NW Libya) - Alakhdar, Abo alkasem (Conference On Engineering Science and Technology, 2021)
Slopes cuts to extend and widen roads contribute to the Slope Failure, These Slope Failure will effect road users; As mentioned above, the cut slopes parallel to the      Al-Meshar road were studied at the Bir Al-Ghanam area, investigating their reality and explaining the factors that effected it. The main objective was to Evaluation the Slope stability of the Slopes cuts, To achieve the objectives, the field study was used and study Mechanical Properties For Discontinuity Surfaces (joints and Fracture) at the field and for Intact Rock at the laboratory, the program (Rocplane v.2.0) was Also Used to Analyze the Stability of The Sliding Level of the  Slopes Expected To Failure, The most important field results were the presence of weak areas that, if neglected, would cause disasters to the road and its users. It was also found that there were rocky interruptions in the slopes, which were caused by the occurrence dissolution of gypsum rocks at the areas of the presence of vertical separators systems S1, S3The values of the joint system were 230 cm with a extremely wide spaced classification, and the durability value of the rock quality designation (RQD) was 78.5% with a good classification It was found that the factor of safety decreases in an inverse relationship with the water saturation. As the saturation increases, the factor of safety decreases, especially at water quantity 25 mm, The most important recommendations of the study are to remove the rock masses and rock debris that fill the interruptions caused by dissolution of gypsum rocks
Keywords: Slope stability; Al-Meshar road; Rocky Interruptions; Landslides; Gypsum Rock